IgE‐mediated regulation of IL‐10 and type I IFN enhances rhinovirus‐induced Th2 differentiation by primary human monocytes. Issue 10 (25th May 2020) - Rowe, Regina K.; Pyle, David M.; Farrar, J. David; Gill, Michelle A.
Abstract: Rhinovirus (RV) infections are linked to the development and exacerbation of allergic diseases including allergic asthma. IgE, another contributor to atopic disease pathogenesis, has been shown to regulate DC antiviral functions and influence T cell priming by monocytes. We previously demonstrated that IgE‐mediated stimulation of monocytes alters multiple cellular functions including cytokine secretion, phagocytosis, and influenza‐induced Th1 development. In this study, we investigate the effects of IgE‐mediated stimulation on monocyte‐driven, RV‐induced T cell development utilizing primary human monocyte‐T cell co‐cultures. We demonstrate that IgE crosslinking of RV‐exposed monocytes enhances monocyte‐driven Th2 differentiation. This increase in RV‐induced Th2 development was regulated by IgE‐mediated inhibition of virus‐induced type I IFN and induction of IL‐10. These findings suggest an additional mechanism by which two clinically significant risk factors for allergic disease exacerbations—IgE‐mediated stimulation and rhinovirus infection—may synergistically promote Th2 differentiation and allergic inflammation. Abstract : IgE‐mediated stimulation of human monocytes enhances rhinovirus‐driven Th2 development while inhibiting Th1 differentiation, shifting the Th1/Th2 balance. These effects are regulated by IgE‐mediated inhibition of virus‐induced type I IFN and induction of IL‐10 and suggest a mechanism by which IgE‐mediated effects and rhinovirus infection synergistically promote allergic inflammation .